Selection of Natural Fiber for Hybrid Kevlar/Natural Fiber Reinforced Polymer Composites for Personal Body Armor by Using Analytical Hierarchy Process - Naveen, J.; Jawaid, M.; Zainudin, E. S.; Sultan, Mohamed T. H.; Yahaya, Ridwan B. (Frontiers in Materials, 2018)
Kevlar 29 is the most widely used synthetic fiber for body armor applications and they have been derived from petroleum based resources. Depletion of petroleum resources and the increase in awareness about the eco-friendly materials encouraged the researchers to explore the potential use of natural fiber as an alternative for synthetic fibers. Hybridization of natural fiber with synthetic fiber will result in unique properties which is difficult to obtain from the individual fibers. In this research Analytical Hierarchy Process (AHP) was used to identify the most suitable natural fiber to be hybridized with Kevlar 29 fiber as a reinforcement in the polymer composites for personal body armor. Fourteen natural fibers and seven criteria's were selected and analyzed for hybridization with respect to the personal body armors design specification. Cocos nucifera sheath which is a naturally woven fiber yields the highest priority vector and it was selected as a most promising natural fiber for hybridization with Kevlar 29 for personal body armor. Eventually, sensitivity analysis was carried out to check the stability of the priority ranking.